PENDIDIKAN KARAKTER DAN PERKEMBANGAN PSIKOLOGI ANAK DALAM DONGENG BURUNG MERPATI DAN SEMUT MERAH - Mauliya Nandra Arif Fani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
This study aims to describe the values of character education in the tale â€œThe Pigeon and The Red Antâ€ that is concerned with child psychology development. This study is qualitative study using descriptive method. This study focus to character in tale â€œâ€œThe Pigeon and The Red Antâ€ that is concerned with child psychology development in the first their growth age. The social values as help each other, care, creative, and response to phenomenon of around that is found in this tale can create good personality for children in develpment of their psychology.